Effect of processing on physico-chemical characteristics of dietary fibre concentrates obtained from peach (Prunus persica L.) peel and pulp - de Escalada Pla, Marina Francisca (2012)
In order to obtain rich dietary fibre concentrateswith enhanced functional properties frompeach peel and pulp,a treatment with ethanol (96% v/v) was performed previous to drying under 30 °C forced air convection for 7 h or under freeze drying. All the dietary fibre concentrates isolatedwere enriched in cell wall polymers and a high polyphenol content was associated to them. The yield of those proceeding from peel almost doubled the one of concentrates obtained from pulp and high hydration capacities were shown by all the concentrates. Fractions from peel showed the darkest colour. Oil holding capacity (1.81–2.4 g/g) was higher than the one reported in bibliography for peach bagasse (1.02 g/g) and quince wastes (1.59 g/g). Concerning the effect of the drying technique used, it was observed that air drying gave origin to pulp dietary fibre concentrates of lower oil holding capacity and less solid behaviour than freeze drying.